Informing ‘good’ global health research partnerships: A scoping review of guiding principles - Erynn M. Monette; David McHugh; Maxwell J. Smith; Eugenia Canas; Nicole Jabo; Phaedra Henley; Elysée Nouvet (Global Health Action)
Background: Several sets of principles have been proposed to guide global health research partnerships and mitigate inequities inadvertently caused by them. The existence of multiple sets of principles poses a challenge for those seeking to critically engage with and develop their practice. Which of these is best to use, and why? To what extent, if any, is there agreement across proposed principles? Objective: The objectives of this review were to: (1) identify and consolidate existing documents and principles to guide global health research partnerships; (2) identify areas of overlapping consensus, if any, regarding which principles are fundamental in these partnerships; (3) identify any lack of consensus in the literature on core principles to support these partnerships. Methods: A scoping review was conducted to gather documents outlining ‘principles’ of good global health research partnerships. A broad search of academic databases to gather peerreviewed literature was conducted, complemented by a hand-search of key global health funding institutions for grey literature guidelines. Results: Our search yielded nine sets of principles designed to guide and support global health research partnerships. No single principle recurred across all documents reviewed. Most frequently cited were concerns with mutual benefits between partners (n = 6) and equity (n = 4). Despite a lack of consistency in the inclusion and definition of principles, all sources highlighted principles that identified attention to fairness, equity, or justice as an integral part of good global health research partnerships. Conclusions: Lack of consensus regarding how principles are defined suggests a need for further discussion on what global health researchers mean by ‘core’ principles. Research partnerships should seek to interpret the practical meanings and requirements of these principles through international consultation. Finally, a need exists for tools to assist with implementation of these principles to ensure their application in research practice.